2019
DOI: 10.35232/estudamhsd.525983
|View full text |Cite
|
Sign up to set email alerts
|

Aşi Redleri̇ni̇n Artmasi Ve Aşi Karşitliğini Etki̇leyen Faktörler

Abstract: Sağlık hizmetlerinin temel amacı, bireylerin sağlığını korumak ve hastalıkları engellemektir. Bulaşıcı hastalıkların önlenmesinde en önemli halk sağlığı uygulamalarından biri aşılamadır. Ülkemizde çocukluk çağı aşılama programlarının başarısı oldukça yüksek olmasına ragmen; aşı uygulamalarına ve etkilerine yönelik son yıllarda artan endişeler dikkat çekmektedir. Aşı uygulamalarına yönelik endişelerin giderilmesi; GBP hedeflerine ulaşılabilmesi, toplumu ölüm ve ciddi komplikasyon riskleri olan hastalıklara karş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 33 publications
0
9
0
9
Order By: Relevance
“…Although there were some changes in the vaccination schedule, the 2018 Turkish demographic health survey reported that the rate of fully vaccinated children was 67% in 2018 and 74% in 2013 (Hacettepe University Institute of Population Studies, 2019). With the decrease in vaccination rates over the years, some diseases, such as whooping cough, measles and diphtheria, have started to reappear (Yüksel & Topuzo glu, 2019). The primary purpose of public health nursing is to protect and improve the health of the community.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were some changes in the vaccination schedule, the 2018 Turkish demographic health survey reported that the rate of fully vaccinated children was 67% in 2018 and 74% in 2013 (Hacettepe University Institute of Population Studies, 2019). With the decrease in vaccination rates over the years, some diseases, such as whooping cough, measles and diphtheria, have started to reappear (Yüksel & Topuzo glu, 2019). The primary purpose of public health nursing is to protect and improve the health of the community.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study conducted on university students receiving health education, it was determined that although there was no significant relationship between sociodemographic characteristics and anti-vaccination, it was determined that students' health education affected their anti-vaccination. Studies have shown that one of the most important reasons for hesitancy about the vaccine is ignorance about the vaccine content, and this gives positive results when the vaccine is informed (Yuksel and Topuzoglu, 2019). Accordingly, the anti-vaccine attitudes of students receiving health education vary according to the education they receive.…”
Section: Discussionmentioning
confidence: 99%
“…Aşılamanın, otizm gelişme riskini artırmadığına dair çok sayıda çalışma yapılmış olmasına rağmen, hâlâ bu endişeler devam etmektedir. [11][12][13] Yine Caudal ve ark. ebeveynlerle yaptıkları çalışmada, ebeveynlerin aşı içerisinde kullanılan adjuvanların yan etkilerinden korkmasından dolayı tereddüt yaşadıklarını belirtmişlerdir.…”
Section: Discussionunclassified